ANALISIS GAYA KEPEMIMPINAN KEPALA SEKOLAH DI MADRASAH ALIYAH NURUL JANNAH PLAMPANG - Novi Kadewi Sumbawati; Abdul Rahim; Abdur Rauf (Samalewa: Jurnal Riset & Kajian Manajemen, 2021)
This study aims to describe the leadership style of principal of MA Nuurul Jannah Plampang.This study was a descriptive qualitative.The subjects in this study were the principal, the head of the foundation, the head of administration, the chairman of the student council and the head of the class X-XII.The data collection technique used in this study was interviews.The data were analyzed using the theory of Miles and Huberman which consists of 4 stages, namely data collection, data reduction, data presentation and drawing conclusions. The results of the study showed that the leadership style implemented by the principal of MA Nuurul Jannah Plampang tends to a democratic leadership style.This can be seen from the way the principal solves problems and took decisions.Solving problems and making decisions were always done through meetings, discussions, and deliberation with staff and teachers.The principal always actively participates in every activity in the school.